Acquired von Willebrand Syndrome in Pediatric Extracorporeal Membrane Oxygenation Patients: A Single Institution's Experience*. Issue 10 (October 2019) - Ruth, Amanda; Meador, Marcie; Hui, Rocky; Loftis, Laura; Teruya, Jun
Abstract : Objectives: 1) Describe the prevalence of acquired von Willebrand syndrome in pediatric patients undergoing extracorporeal membrane oxygenation deemed to be at increased risk for the disease in our institution, 2) discuss the challenges of testing for acquired von Willebrand syndrome diagnosis, 3) describe the characteristics of the patient population found to have acquired von Willebrand syndrome and their outcomes, and 4) discuss the potential implications of acquired von Willebrand syndrome on bleeding complications. Design: Retrospective chart review. Setting: PICU and cardiovascular ICU in a single institution. Patients: All PICU and cardiovascular ICU extracorporeal membrane oxygenation patients 0–18 years old who underwent screening for acquired von Willebrand syndrome between January 2014 and December 2016. Interventions: Humate P administration to a small subset of acquired von Willebrand syndrome positive subjects. Measurements and Main Results: Laboratory data of identified patients were analyzed. The diagnosis of acquired von Willebrand syndrome was made based on decreased ristocetin cofactor activity to von Willebrand factor antigen ratio and/or abnormal multimer analysis. Clinical data were extracted from the chart and through the Pediatric Extracorporeal Membrane Oxygenation Outcome Registry to describe the demographics, comorbidities, and outcomes of this patient population. In the 2 years, 29 patients had laboratory testing performed for surveillance and in cases of clinical bleeding. Of these, 23 (79%) were positive by criteria. No significant difference in mortality rate was found between patients with acquired von Willebrand syndrome versus without. We also did not find a significant difference in the blood product utilization or bleeding complications between patients with acquired von Willebrand syndrome versus without. Humate P was administered in 39% of patients (9/23) who were positive for acquired von Willebrand syndrome, but no significant difference was seen in blood product utilization or bleeding complications between acquired von Willebrand syndrome patients receiving Humate P versus those who did not. Conclusions: Acquired von Willebrand syndrome is a common but under recognized disorder in pediatric extracorporeal membrane oxygenation patients. The clinical implications of this disorder on bleeding and its potential treatments are still unclear.